Is non-alcoholic fatty liver disease a sign of left ventricular diastolic dysfunction in patients with type 2 diabetes mellitus? A systematic review and meta-analysis. Issue 1 (20th February 2023) - Wang, Sicheng; Zhang, Xiangyuan; Zhang, Qiqi; Zhang, Boxun; Zhao, Linhua
Abstract : Recent studies have associated non-alcoholic fatty liver disease (NAFLD) with impaired cardiac function. However, patients with type 2 diabetes mellitus (T2DM), a high-risk group for left ventricular diastolic dysfunction (LVDD), were not analyzed as an independent study population. A systematic review was conducted to identify all published clinical trials using the PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, and Wanfang databases from inception to September 14, 2022. Observational studies that reported echocardiographic parameters in T2DM patients with NAFLD compared with those without NAFLD were included for further selection. The Agency for Healthcare Research and Quality checklist was used to appraise the study quality. Ten observational studies (all cross-sectional in design) comprising 1800 T2DM patients (1124 with NAFLD, 62.4%) were included. We found that T2DM patients with NAFLD had a significantly lower E/A ratio, higher peak A velocity, higher E/e' ratio, lower e' velocity, greater left atrial maximum volume index, and greater left ventricular mass index than non-NAFLD patients. These findings reinforced the importance of NAFLD being associated with an increased risk of LVDD in the T2DM population, and NAFLD may be a sign of LVDD in patients with T2DM. PROSPERO registration number CRD42022355844.